1986
DOI: 10.1523/jneurosci.06-08-02240.1986
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid toxicity in the hippocampus: reversal by supplementation with brain fuels

Abstract: Glucocorticoids (GCs) can damage neurons of the hippocampus, the principal target tissue in the brain for the hormone. Hippocampal neuron loss during aging in the rat is accelerated by prolonged GC exposure and decelerated by adrenalectomy. GCs appear to damage these neurons indirectly by inducing a state of vulnerability and thus impairing their capacity to survive a variety of metabolic challenges. As such, high physiological concentrations of the steroid increase hippocampal damage induced by an antimetabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
8

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(124 citation statements)
references
References 21 publications
(13 reference statements)
6
109
1
8
Order By: Relevance
“…Indeed, it has been suggested that prolonged overproduction of glucocorticoids, whether as a result of ongoing stress or a genetic predisposition to HPA axis hyperactivity, damages brain structures (especially the hippocampus) essential for HPA axis restraint. 41 Such damage, in turn, has been hypothesized to lead to a feed-forward circuit in which ongoing stressors drive glucocorticoid overproduction indefinitely (the "glucocorticoid cascade hypothesis"). Because of the capacity of high concentrations of glucocorticoids to disrupt cellular functioning in ways that can lead to a host of ills, this glucocorticoid overproduction is believed to contribute directly to many of the adverse behavioral and physiological sequelae associated with chronic stress.…”
Section: Abnormalities Of Hpa Axis In Depressionmentioning
confidence: 99%
“…Indeed, it has been suggested that prolonged overproduction of glucocorticoids, whether as a result of ongoing stress or a genetic predisposition to HPA axis hyperactivity, damages brain structures (especially the hippocampus) essential for HPA axis restraint. 41 Such damage, in turn, has been hypothesized to lead to a feed-forward circuit in which ongoing stressors drive glucocorticoid overproduction indefinitely (the "glucocorticoid cascade hypothesis"). Because of the capacity of high concentrations of glucocorticoids to disrupt cellular functioning in ways that can lead to a host of ills, this glucocorticoid overproduction is believed to contribute directly to many of the adverse behavioral and physiological sequelae associated with chronic stress.…”
Section: Abnormalities Of Hpa Axis In Depressionmentioning
confidence: 99%
“…This agrees with findings that energy supplementation can reverse GC exacerbation of neurotoxicity induced by kainate and ischemia (Tombaugh and Sapo!sky, 1992) in the hippocampus. In these latter articles, the energy supplementation took the form of mannose and ketones as well as glucose (Sapolsky, 1986). The generality of these interventions suggests that the energetic features of glucose supplementation ultimately help maintain ATP levels.…”
Section: The Cells In the Mitochondrial Potential Experimentsmentioning
confidence: 99%
“…They do so regardless of their peripheral catabolic actions, since the aggrevation of induced lesions was also observed in isolated brain preparations Tombaugh et al, 1992). Additional administration of energy sources, such as glucose or mannose, effectively protected against the deleterious effects of glucocorucolos (Sapolsky, 1986). Considering the implication of increased excitatory amino acid transmission, particularly through NMDA receptors, and a :~teady elevation of intracellular [Ca] in neuronal damage due to energy shortage, it is not surprising that the glucocorticoid-induced exacerbatmn of neurotoxic agents shows NMDA and Ca dependenc~,: !l) Corticosterone enhanced 3AP toxicity was reduced by a NMDA antagonist (Armanini cz al., 1990): rapid changes in glucose utilization after mild stress are also NMDA-dependent (Schasfoort <: al.. 1988) (2) Kainic acid-evoked rises in [Ca]~ in a hippocampal neuronal culture are enhanced alter 24 hr incubation with 1 #M corticosterone (Elliot and Sapolsky, 1992), at least partly due t~ an impaired Ca-extrtlsion mechanism (Elliot and Sapolsky, 1993).…”
Section: Metabolically Regulated Characteristicsmentioning
confidence: 99%